DECODING THE IRREGULARITY IN THE CASBAH URBAN FABRIC - Mohammed Brahimi,; Mustapha Benhamouche, (International Journal of Innovative Technologies in Social Science, 2023)
This study aims at explaining how the urban fabric of the Casbah City (Algiers) emerged and the mechanisms that produced such an urban pattern. The research focuses on the study of the impact of some Islamic laws; preemption, inheritance, the right of precedence, and endowments (waqf) on the morphology of streets, plots and blocs that constitute the irregular urban fabric. The study relies on the old maps of the Casbah and its topography to illustrate such physical and spatial impact. It concludes that the urban fabric was the result of the symbiosis of natural factors, mainly the terrain, the orientation and the waterways, and the legal mechanisms that turned into social practices. This paper can help students of architecture and urban planning understand how the urban fabric of Casbah was constructed.